(3YhGQa GdeYGQas - (3TgGH GdOjf CHh MaU YeQ Hf eMeO Hf YHO Gddg GdSgQhQOj GdTGaYj, GdSgQhQOj,J (B632 (3g` s ((3CMeO Hf eMeO Hf YHO Gddg GdfXGei GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdYXje TGfg Gdbhi SdWGfg GdXGgQ EMSGfg GdHGFfI MLJg hHQgGfg s
(3BNQgG (B:s
(3Je cJGHI MGeOG ddg JYGdi Ydi BdGFg heUdjG Ydi eMeO NGJe CfHjGFg s
(3GdfSNI HgG MhGTs
(3Ydi dhMI GdYfhGf Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1177s
Keywords: (3GdJUha hGdBOGH GdTQYjIs